Suppression of the LKB1-AMPK-SLC7A11-GSH signaling pathway sensitizes NSCLC to albumin-bound paclitaxel via oxidative stress - Dade Rong; Liangliang Gao; Yiguan Chen; Xiang-Zheng Gao; Mingzhu Tang; Haimei Tang; Yuan Gao; Guang Lu; Zhi-Qiang Ling; Han-Ming Shen (Redox Biology)
Albumin-bound paclitaxel (nab-PTX) is an important chemotherapeutic drug used for the treatment of advanced and metastatic non-small cell lung cancer (NSCLC). One critical issue in its clinical application is the development of resistance; thus, a deeper understanding of the mechanisms underlying the primary resistance to nab-PTX is expected to help to develop effective therapeutic strategies to overcome resistance. In this study, we made an unexpected discovery that NSCLC with wild-type (WT) Liver kinase B1 (LKB1), an important tumor suppressor and upstream kinase of AMP-activated protein kinase (AMPK), is more resistant to nab-PTX than NSCLC with mutant LKB1. Mechanistically, LKB1 status does not alter the intracellular concentration of nab-PTX or affect its canonical pharmacological action in promoting microtubule polymerization. Instead, we found that LKB1 mediates AMPK activation, leading to increased expression of SLC7A11, a key amino acid transporter and intracellular level of glutathione (GSH), which then attenuates the production of reactive oxygen species (ROS) and apoptotic cell death induced by nab-PTX. On the other hand, genetic or pharmacological inhibition of AMPK in LKB1-WT NSCLC reduces the expression of SLC7A11 and intracellular GSH, increases ROS level, and eventually promotes the apoptotic cell death induced by nab-PTX in vitro. Consistently, the combination of nab-PTX with an AMPK inhibitor exhibits a greater therapeutic efficacy in LKB1-WT NSCLC using xenograft models in vivo. Taken together, our data reveal a novel role of LKB1-AMPK-SLC7A11-GSH signaling pathway in the primary resistance to nab-PTX, and provide a therapeutic strategy for the treatment of LKB1-WT NSCLC by targeting the LKB1-AMPK-SLC7A11-GSH pathway.